The prognostic value of neutrophil-to-lymphocyte ratio on mortality in critically ill trauma patients. Issue 5 (November 2016) - Dilektasli, Evren; Inaba, Kenji; Haltmeier, Tobias; Wong, Monica D.; Clark, Damon; Benjamin, Elizabeth R.; Lam, Lydia; Demetriades, Demetrios
Abstract : BACKGROUND: Recent studies suggest that the neutrophil-lymphocyte ratio (NLR) as a marker of inflammation is associated with mortality in surgical patients. The aim of this study was to determine the prognostic impact of NLR in critically ill trauma patients. METHODS: This is a retrospective cohort study involving all trauma patients 16 years or older admitted to the surgical intensive care unit of a Level 1 trauma center (January 2013 to January 2014). The predictive capacity of NLR on mortality was assessed using a receiver operating characteristic curve analysis. To identify the effect of the NLR on survival, a separate log-rank test was used. Multivariable Cox proportional hazard modeling was used to identify independent predictors of mortality. RESULTS: During the study period, 1, 356 patients met inclusion criteria. Of these, 74% were male, 86% sustained blunt trauma, and the median age was 49 years (interquartile range [IQR], 35). The median Glasgow Coma Scale (GCS) score and Injury Severity Score (ISS) were 15 (IQR, 3) and 13 (IQR, 14), respectively. With the use of the receiver operating characteristic curve analyses at intensive care unit Days 2 and 5, optimal NLR cutoff values of 8.19 and 7.92 were calculated by maximizing the Youden index. Kaplan-Meier curves revealed an NLR greater than or equal to these cutoff values as a marker for increased in-hospital mortality ( p < 0.001, log-rank test). The Cox regression model demonstrated that an NLR greater than 8.19 and 7.92 are independently associated with in-hospital mortality at Days 2 and 5, respectively (hazard ratio, 1.602 [ p = 0.019] and 3.758 [ p < 0.001]). CONCLUSION: NLR is associated with mortality in critically ill trauma patients. Prospective validation of its role as a predictive marker for outcomes is warranted. LEVEL OF EVIDENCE: Prognostic study, level III.